The Evaluation of Challenges of Youth in Kazakhstan and Piloting Innovative Solutions - Sagintayeva, Aida; Ibrasheva, Alima; Yedgenov, Bauyrzhan; Yelubayeva, Galiya; Tyutyunnikova, Marina; Akpayeva, Aliya; Jumakulov, Zakir (Nazarbayev University Graduate School of Education, 2024)
In the ever-evolving landscape of youth development and social policy, the issue of NEET youth—those not in education, employment, or training—presents a critical challenge that demands thoughtful analysis and innovative solutions. Over the last two decades, Kazakhstan has made substantial strides in addressing this concern, witnessing a commendable reduction in the number of NEET youths from 18.6% in 2001 to 6.3% in 2022. The government's dedication to shaping policies that facilitate the socialization, employment, and education of young individuals is evident in the extensive programs implemented to provide holistic support, from free education to mentorship initiatives. Through a combination of qualitative methods, literature reviews, and groundbreaking experiments in experimental economics—both in laboratories and field settings—the researchers delve deep into the challenges faced by NEET youth in Kazakhstan. The inclusion of innovative approaches, particularly in Central Asia, the Caucasus, and Eastern Europe, sets a pioneering precedent for future studies in the region.
Keywords: NEET youth, Kazakhstan, evaluation